Mental Health Support in the Time of Crisis: Are We Prepared? Experiences With the COVID-19 Counselling Programme in Hungary - Szlamka, Zsófia; Kiss, Márta; Bernáth, Sámuel; Kámán, Péter; Lubani, Amina; Karner, Orsolya; Demetrovics, Zsolt (Frontiers in Psychiatry, 2021)
The Coronavirus disease 2019 (COVID-19) posed unexpected global economic and societal challenges. These include a heavy impact on mental health due to fast changing lockdown and quarantine measures, uncertainty about health and safety and the prospect of new waves of infections. To provide crisis mental health support during the pandemic, Eötvös Loránd University in Hungary launched a specialist online counselling programme, consisting of one to three sessions. Overall, 47 clients received support. In this paper we discuss challenges reported by clients, key features of providing a brief mental health intervention online, reflect on counsellor experiences. Most clients had challenges with developing a daily routine under quarantine; and many had hardship related to finances, housing, and distance learning. Common mental health consequences included fear from the virus and stress, anxiety, and fatigue due to the interruption to everyday life. In some cases, more complex conditions were triggered by the pandemic. Examples include addictive behaviours and symptoms of depression or psychosis. However, referring cases beyond the competency of counselling proved to be a challenge due to the closure of specialist services. Counsellors observed three key features to the online delivery of a brief crisis mental health intervention: 1) an explicit problem-oriented approach to counselling; 2) challenges of building rapport online; and c) frames of online counselling. Counsellor experiences often overlapped with those of clients and included challenges of working from home and adjusting to online counselling methods. Like other mental health initiatives launched to tackle COVID-19, the intervention’s effectiveness was not measured given the unexpected context and short time frame for programme development. We recommend the use of impact measurement tools to develop mental health services in crises. Meanwhile, the pandemic brought to attention the need to better understand online delivery models. Counsellors should have access to training opportunities on online counselling and managing work-life balance in a remote setting. Clearly, more studies are needed discussing delivery models and effectiveness of mental health interventions during the pandemic. Experience and knowledge sharing across practitioners should be encouraged to improve how the field reacts to unexpected, high risk events and crises.